Psychological aspects of fetal alcohol syndrome prevention in pregnant women of childbearing age - E. A. Burina; A. Y. Marianian (Acta Biomedica Scientifica, 2018)
The article observes the study results of knowledge, attitudes and alcohol behavior in pregnant women within fetal alcohol prevention program in childbearing age women. The theoretical and methodological basis of the study is Health Belie/Model and the method of dual-focused brie/ intervention. The study was conducted on the basis of the psychology department ofSaint Petersburg State University. Data were collected in 10 women's consultation clinics ofSaint Petersburg. The sample included 280 women of childbearing age. Methods of psychological research are presented by materials developed by the «FAS research team» according to the study goals. The results showed that the developed preventive program and its components (brief intervention and passive information] achieve their main goal, program implementation reduces or stops the use of alcohol by pregnant women, in other words, it virtually eliminates the risk of developing FAS and FASD in a future child. This program was carried out as a part of the project supported by grant R01AA016234 «Prevention of FASD in Russian Children», principal investigator: Tatiana N. Balachova, The University of Oklahoma Health Sciences Center (USA), from the NIH / National Institute on Alcohol Abuse and Alcoholism and Fogarty International Center.